DISCRETE DYNAMIC MODEL OF BEVEL GEAR – VERIFICATION THE PROGRAM SOURCE CODE FOR NUMERICAL SIMULATION - Krzysztof TWARDOCH (Scientific Journal of Silesian University of Technology. Series Transport)
In the article presented a new model of physical and mathematical bevel gear to study the influence of design parameters and operating factors on the dynamic state of the gear transmission. Discusses the process of verifying proper operation of copyright calculation program used to determine the solutions of the dynamic model of bevel gear. Presents the block diagram of a computing algorithm that was used to create a program for the numerical simulation. The program source code is written in an interactive environment to perform scientific and engineering calculations, MATLAB